IDENTIFICATION OF NUTRITIONAL STATUS IN PRE-ADOLESCENT GROUP IN THE INTEGRATED ISLAMIC ELEMENTARY SCHOOL AL FIRDAUS PURWODADI - Pintam Ayu Yastirin; Rosmala Kurnia Dewi (Jurnal Profesi Bidan Indonesia, 2022)
Background: As many as 46 million people (17%) of the total population of productive age in Indonesia are in the adolescent age group (10-19 years), with a classification of 48% female adolescents and 52% male adolescents. In Indonesia, the prevalence of nutritional status based on BMI/U in the population aged 5-12 years is 2.4% very thin, 6.8% thin, 10.8% fat and 9.2% obese. While the prevalence of nutritional status based on height / age, 6.7% very short and 16.9% short. Purpose: describe the nutritional status of the pre-adolescent group. Method: The research design uses a cross-sectional study, through physical examination and documentation studies. The research sample was conducted using a random sampling technique of 50 students, and analyzed using descriptive analysis. Results: The research results revealed that 58% of the 50 student samples were female, and based on the results of examination of weight and height, the prevalence of nutritional status of the 50 student samples, the majority of 82% had good nutritional status. Conclusion: Gender is an internal factor that determines nutritional needs, so there is a relationship between gender and nutritional status. In standard anthropometric assessment of children's nutritional status based on BMI/U at the age of   5 to 18 years is used to determine the categories of malnutrition, undernutrition, good   nutrition, over nutrition and obesity